2017
DOI: 10.1002/ijgo.12291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of follicular diameter at the time of ovulation triggering on pregnancy outcomes during intrauterine insemination

Abstract: The optimal follicular diameter associated with increased pregnancy rates in gonadotropin-stimulated IUI cycles was between 19 and 20 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Previous studies have focused on the impact of hormonal stimulation and follicle size on IUI outcome and the outcome of ART. However, there is little data on the influence of spermiogram parameters on the conception probability of women undergoing fertility treatment by IUI [4][5][6] . Custers et al investigated 391 women who received an IUI and either got up immediately afterwards or remained lying for 15 minutes 2 .…”
mentioning
confidence: 99%
“…Previous studies have focused on the impact of hormonal stimulation and follicle size on IUI outcome and the outcome of ART. However, there is little data on the influence of spermiogram parameters on the conception probability of women undergoing fertility treatment by IUI [4][5][6] . Custers et al investigated 391 women who received an IUI and either got up immediately afterwards or remained lying for 15 minutes 2 .…”
mentioning
confidence: 99%
“…Of the remaining 375 papers, 117 did not classify a definition of unexplained infertility. As a result, a total of 258 primary research papers with full text available were included …”
Section: Resultsmentioning
confidence: 99%
“…and Liu et al. found that endometrial thickness contributed to the success rate in IUI cycles ( 25 , 26 ), other studies found no evidence for an association between endometrial thickness and pregnancy rates during IUI ( 27 ).…”
Section: Discussionmentioning
confidence: 96%